CRIMINAL NON-PROSECUTION AGREEMENT AS A INSTRUMENT FOR EXPANSION OF NEGOTIATION SPACES IN THE BRAZILIAN LEGAL SYSTEM AND MEANS OF EFFECTIVE CITIZENSHIP (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
ABSTRACT The enactment of Law 13.964/2019, widely known as the Anti-Crime Package, promoted several changes and updates in the Brazilian legal system. One of the biggest advances addressed by the legal text refers to the formal insertion of article 28-A, in the Criminal Procedure Code, regulating the non-prosecution criminal agreement (ANPP), object of study of this work. The possibility of agreement already had a forecast for its application in Resolution nº 181/2017, of the National Council of the Public Ministry, however, surrounded by questions about its efficiency and whether its use is correct in specific cases. The implementation of the device, in the procedural code, formalized the institute in Brazil, solving the questions about its unconstitutionality, in addition to adapting some of its formalities, in order to benefit the parties that agree to it. Objectively, the non-persecutory agreement represents a type of negotiation between the accused and the prosecution, having a decriminalizing character. With the offer of the agreement to the investigated and its acceptance, the consequence is the non-continuation of the process, preventing the offering of the complaint and other procedural acts. The ANPP is distinguished by the fact that its elements differ from the other types of agreement already foreseen, because it is the discretion of the Public Ministry, supported by the family of the agreement, to some in which the confession of the accused is essential. This new negotiation modality expanded the field of negotiation justice in Brazil, providing greater effectiveness to the Brazilian penal system.  Key-words: Criminal Non-Persecution Agreement. Anti-Crime Package. Consensual Justice.